Effect of yacon flour (Smallanthus sonchifolius) consumption on body weight, body composition, intestinal permeability and metabolic changes in excess body weight adults - Machado, Adriane Moreira (2019)
Yacon root is a natural source of fructooligosaccharides (FOS) and phenolic compounds. However, it has short shelf life due to its high water content. In this sense, the yacon flour becomes promising, because in addition to increasing the shelf life of the yacon, it presents a higher concentration of bioactive compounds in a smaller portion of product when compared to the root. The effect of yacon flour consumption on metabolic markers has not been studied in excess body weight adult humans. Thus, we evaluated the effect of the consumption of yacon flour associated with an energy restricted diet on body composition, food intake, intestinal function, biochemical variables concentration, intestinal permeability, fecal short chain fatty acids, oxidative stress and inflammatory markers concentrations in adults with excess body weight. A randomized, parallel arm study involving 26 adults (11 men and 15 women, mean age 31.3 ± 8.5 years) with excess body weight (mean body mass index 30.4 ± 2.4 kg / m²) was conducted. Subjects were allocated to one of the two experimental groups (control (n= 13) or yacon flour (n = 13)), received the prescription of energy-restricted diets (- 500 kcal / day) and daily consumed a breakfast drink not containing or containing 25 g of yacon flour. At the beginning and at the end of the study, anthropometrics, body composition, blood pressure, biochemical analyses, intestinal function, food intake, intestinal permeability, inflammatory and oxidative stress markers concentrations were assessed. Antioxidant capacity was evaluated in vitro. Furthermore, the flour chemical characterization, FOS and total phenolics contents were evaluated. Daily consumption of 25g of yacon flour was well tolerated, did not cause adverse gastrointestinal effects, increased dietary fiber consumption, improved stool consistency, reduced constipation frequency and promoted greater body weight, waist circumference, waist to height index, sagittal abdominal diameter, and body fat reductions. In addition to these results, there was also a reduction in fecal SCFA and protein carbonyl concentrations besides increasing plasma total antioxidant capacity. Considering the results observed in the present study, it can be inferred that yacon flour is a good source of fiber (FOS) and it seems to have a positively manage excess body weight.